Physical Activity Interventions for Individuals With a Mild Traumatic Brain Injury: A Scoping Review. Issue 3 (May 2021) - Alarie, Christophe; Gagnon, Isabelle; Quilico, Enrico; Teel, Elizabeth; Swaine, Bonnie
Abstract : Objective: To document the characteristics, measured outcomes, and effectiveness of physical activity (PA) interventions designed to improve health-related outcomes in individuals with a mild traumatic brain injury (mTBI) to assist in rehabilitation quality improvement efforts of a TBI rehabilitation program. Methods: A scoping review following a 6-step iterative framework search across 5 databases (MEDLINE, CINAHL, PsycINFO, SPORTDiscuss, and EMBASE) and the gray literature (Google) was performed. Selected PA interventions were designed for individuals of all ages and any mechanism of injury (eg, sports-related and falls). Data were charted, collated, and summarized according to the Consensus on Exercise Reporting Template checklist and domains of the International Classification of Functioning, Disability and Health. Involvement of clinical experts ensured tailoring of the knowledge synthesis to meet clinical needs. Results: Thirty-five articles and 14 gray literature records were retained. Five types of PA interventions were identified with the majority being multimodal. Reporting of PA intervention characteristics was highly variable across studies; many details necessary for intervention replication are missing. Study outcomes focused primarily on improving body functions and symptoms of mTBI, and less frequently on activities, participation, and health-related quality of life. The methodological quality of studies varies. Conclusions: Identified PA intervention types offer various management options for healthcare providers. PA interventions may improve a wide range of health-related outcomes supporting the inclusion of PA in the management of individuals of all ages with mTBI. Higher-quality research and better reporting about intervention characteristics is however needed. Abstract : Supplemental Digital Content is Available in the Text.